Semen Cuscutae flavonoids activated the cAMP-PKA-CREB-BDNF pathway and exerted an antidepressant effect in mice - Shao, Qianfeng; Li, Yue; Jin, Lin; Zhou, Sheng; Fu, Xiaowei; Liu, Tong; Luo, Guangbin; Du, Shaohui; Chen, Che (Frontiers in Pharmacology, 2024)
Background: Semen Cuscutae flavonoids (SCFs) constitute a class of metabolites of Semen Cuscutae, a botanical drug that was recently found to have an anti-depression effect. This study aimed to evaluate the anti-depression effects of SCFs in chronic unpredictable mild stress (CUMS)-induced mice and to interrogate the underlying mechanisms. Materials and methods: The CUMS mice were used for assessing the effects of SCFs treatments on depression. Mice were randomly divided into five groups. Four groups were subjected to the CUMS induction and concomitantly administered orally with either the vehicle or with a high-, medium-, and low-dose of SCFs, once per day for four weeks. One group was kept untreated as a control. The mice were then assessed for their statuses of a number of depression-related parameters, including body weight, food intake, sucrose preference test (SPT), open field test (OFT), tail suspension test (TST), and forced swim test (FST). In addition, a day after the completion of these tests, biopsies from the hippocampus were harvested and used to perform metabolomics by HPLC-MS/MS and to assess the levels of cAMP by ELISA and the levels of PKA, CREB, p-CREB, and BDNF by Western blot analyses. Results: SCFs resulted in significant increases in both body weight and food intake and in the amelioration of the depressive-like behaviors in CUMS mice. A high-dose SCFs treatment led to significant alterations in 72 metabolites, of which 26 were identified as potential biomarkers for the SCFs treatment. These metabolites are associated with lipid, amino acid, and nucleotide metabolism. Among 26 metabolites, cAMP was positively correlated with body weight, SPT, OFT-total distance, and OFT-central residence time, while negatively correlated with immobility time in TST and FST, linking a change in cAMP with the SCFs treatment and the significant improvement in depressive symptoms in CUMS mice. Further analyses revealed that the levels of cAMP, PKA, CREB, p-CREB, and BDNF were reduced in the hippocampus of CUMS mice but were all increased following the SCFs treatments. Conclusion: SCFs could ameliorate hippocampal metabolic disturbances and depressive behaviors and cause the activation of the cAMP-PKA-CREB-BDNF signaling pathway in the hippocampus of CUMS mice.